Synthesis of Cyclic Diglycerols: The Utility of the BF3·OEt2-Mediated Intramolecular Epoxide Ring-Opening Reaction for the Cyclic Polyglycerol Synthesis - Hamada, Masahiro; Noda, Mizuki; Saeki, Yu; Nakajima, Noriyuki (Synthesis, 2025)
We report the synthesis of cyclic diglycerols, which are the smallest repeating units in polyglycerols. Linear diglycerol epoxy alcohols are treated with a catalytic amount of boron trifluoride–diethyl ether complex (BF3·OEt2) in highly dilute dichloromethane (CH2Cl2) to give the corresponding 1,4-dioxepane- and 1,4-dioxane-type cyclic diglycerols in high yields as single structural isomers. The structures of the cyclic products are determined by 1D and 2D NMR spectral analysis. The observed results indicate that the cyclizations are consistent with Baldwin’s rules. The synthesized cyclic diglycerols can serve as standards for further studies.
Keywords: cyclic diglycerols; epoxide ring opening; cyclization; regioselectivity; substitution